Beekeeping and Bee Conservation Advances in Research - Dechechi Chambo, Emerson (IntechOpen, 2016)
Beekeeping and Bee Conservation - Advances in Research presents current issues in the field of bees in multiple contexts and ties together experiments conducted by some of the world's most renowned researchers. The authors' point-of-view and own research results are described in a clear and objective way, which is very useful for beginners in the study of the subject and is likewise valuable for the more experienced on the subject, who may find new hypotheses to be tested and broaden their future prospects in the field. The book is wide in scope, focusing largely on Apis mellifera. Topics range from genetics, to pollination studies, to the conservation of bees. It includes a chapter dedicated to stingless bees and another for bumble bees.